A review of the botany, metabolites, pharmacology, toxicity, industrial applications, and processing of Polygalae Radix: the “key medicine for nourishing life” - Kuang, Hongtuo; Kong, Lingping; Hou, Ajiao; Yang, Anni; Jiang, Hai (Frontiers in Pharmacology, 2024)
Polygalae Radix (PR), the dried root of Polygala tenuifolia Willd. and Polygala sibirica L., which enjoys the reputation for the "key medicine for nourishing life". In this study, "Polygala tenuifolia Willd.", "Polygala sibirica L." and "Yuanzhi" were retrieved in the scientific databases including Google Scholar, Baidu Scholar, Web of Science, PubMed, CNKI and Wan Fang Data to obtain useful information. The information from Chinese herbal medicine classics, Yaozhi Data and Gaide Chemical Network was also collected. The selected information related to its botany, phytochemistry, pharmacology, toxicity, industrial applications, processing were summarized in this paper to tap its potentialities and promote its further development and clinical application. More than 320 metabolites have been isolated from PR, saponins, xanthones, and oligosaccharide esters are main functional metabolites. Pharmacological research shows that its pharmacological action mainly focuses on resisting nervous system diseases, and it also has the functions of antioxidation, anti-inflammation, anti-tumor and anti-pathogenic microorganisms and others. The gastrointestinal irritation of its saponins impeded its application, which can reduce by controlling the dosage, compatibility with other herbs or processing. The future progress of PR faces opportunities and challenges. The traditional application and processing methods of PR recorded in ancient books should be paid more attention to. The lack of safety and clinical studies limited its application and transformation of achievements. Moreover, it is one-sided to take the content of several metabolites as the index of processing optimization and quality control, which can't reflect the pharmacological and toxicological activities of PR.